Exploring the political chessboard of Syria: an analysis of the role of the US, Russia, Iran and Turkey through the lens of realism(s) - Cunha, Joana Filipa Prata e (2021)
The Syrian war has played a major role in current international political affairs since 2011. What started as a peaceful revolution soon turned into a civil war: the escalation of violence, the rise of the death toll and the displacement of millions of people within and outside the country triggered the intervention of external state and non-state actors. Given their significant contribution to decision-making and policymaking in Syria, this dissertation aims to investigate how the involvement of the United States, Russia, Iran and Turkey impacted the developments of the Syrian war. Based on the core principles and theoretical tools of realism, neorealism and neoclassical realism and on the different perceptions of security in the defensive and offensive realism(s), we aim to explore how the interests and goals of each state can particularly explain their participation and contribution to the complexification of the Syrian war between 2011 and 2018. We conclude that the development of the events in the Syrian civil war triggered the involvement of each state, which, in turn, made a possible resolution of the conflict increasingly more difficult due to the distinct interests and goals of each state's political agenda.